Trajetórias em movimento: vivências sociais e laborais de imigrantes haitianos - Faccin, Rodrigo Duarte (2021)
The present thesis seeks to understand the experiences and trajectories of Haitian immigrants residing in the municipality of Vacaria, Rio Grande do Sul, highlighting the insertions of this public in the destination society and in the job market, resorting to the combination of different techniques and procedures of research, such as interview, observation, documentary research, bibliographic research and content analysis. In this context, it was observed that after facing long displacements, Haitian immigrants seek, from entering the job market, a possibility to rebuild their lives. However, they are allocated to temporary rural jobs, due to the need of both parties, the contractors and the contractors themselves. The temporary nature of rural work, in some cases consisting of daily contracts, prevents labor and, consequently, economic stability. The non-belonging to the place where they are located and the estrangement of the local population, added to the fact that they are absent in their country of origin, establish a complex drama experienced by these individuals.